2021
DOI: 10.31234/osf.io/sur2j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing Personality Traits with the Help of a Digital Personality Change Intervention

Abstract: Personality traits predict important life outcomes such as success in love and work life, wellbeing, health, and longevity. Given these positive relations to important outcomes, economists, policy-makers, and scientists have proposed intervening to change personality traits to promote positive life outcomes. However, non-clinical interventions to change personality traits are lacking so far in large-scale naturalistic populations. This study (N = 1,523) examined the effects of a 3- month digital personality ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Combined with additional findings in chronic pain populations including those described here, dispositional traits provide an overarching conceptualization to encompass a vast array of psychological, physiological, and behavioral pain-related predictive factors [19,27,28]. Additionally, as dispositional traits are not pathologically-based, they provide the opportunity to communicate about an individual's functional style highlighting strengths as well as identifying vulnerabilities to target to boost resilience [59].…”
Section: Discussionmentioning
confidence: 89%
“…Combined with additional findings in chronic pain populations including those described here, dispositional traits provide an overarching conceptualization to encompass a vast array of psychological, physiological, and behavioral pain-related predictive factors [19,27,28]. Additionally, as dispositional traits are not pathologically-based, they provide the opportunity to communicate about an individual's functional style highlighting strengths as well as identifying vulnerabilities to target to boost resilience [59].…”
Section: Discussionmentioning
confidence: 89%
“…This has important implications for the coaching of teachers in training and practicing teachers. That is, although it is possible to change one’s personality traits volitionally and in an enduring way, this is no easy task (see, e.g., Baranski et al., 2020; Hudson & Fraley, 2015; Stieger et al., 2021). Instead, modifying individuals’ subjective and possibly biased interpretations of their environment may be more feasible, for example, by identifying those situation perceptions that may lead to maladaptive behaviors and developing cognitive strategies or thinking styles to modify those perceptions (Wood et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changes that resulted from therapy not only happened quickly but also remained in place well after patients left therapy. Subsequent research has shown that the other trait domains can also be changed through intervention even if the population or intervention is not clinical in nature (Stieger et al, 2021).…”
Section: Personality Processmentioning
confidence: 99%
“…More importantly, especially from a policy standpoint, personality changes not only happen, but predict important life outcomes, such as job attainment and income (Hoff et al, 2021). Moreover, personality is changeable (Stieger et al, 2021), which leads to the conclusion that it is a viable target for intervention (Bleidorn et al, 2020). And, finally, while some have ethical reservations about the idea of changing personality (English & Carstensen, 2014), it is more often the case that when we seek to change ourselves or others, our goal is, at the very least, a personality-like change (Roberts, Hill, & Davis, 2017).…”
Section: Basic Research Issuesmentioning
confidence: 99%